2000
DOI: 10.1177/0146167200262006
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of Power: Interpersonal Consequences of Differential Power and Expectancies

Abstract: The cognitive and behavioral effects of perceived power and expected partner competence were examined in a task-oriented dyadic interaction. Specifically, the authors manipulated the effects of power and expectancy on social information processing during and subsequent to a dyadic problem-solving interaction. In addition, dispositional power orientation was measured. Results indicated that perceiver power led to self-enhancement and derogation of the target and both perceiver and target awareness of perceiver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 43 publications
(91 reference statements)
0
31
0
Order By: Relevance
“…Previous research has shown that people also consider their roles (Olekalns 1991), their individual values (Coleman 1998), their own and others' personalities (Anderson and Berdahl 2002;Georgesen and Harris 2000), and the time horizon for the relationship with the respective other (Larson 1992) when determining their power. Our research also raises, but does not address, questions about the effect of different sources of power on people's evaluation of the power relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that people also consider their roles (Olekalns 1991), their individual values (Coleman 1998), their own and others' personalities (Anderson and Berdahl 2002;Georgesen and Harris 2000), and the time horizon for the relationship with the respective other (Larson 1992) when determining their power. Our research also raises, but does not address, questions about the effect of different sources of power on people's evaluation of the power relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The $55 amount was deliberately chosen so as to be more difficult to divide evenly. This manipulation of power has been demonstrated effective in several past studies Georgesen & Harris, 2000).…”
Section: Power Manipulationmentioning
confidence: 92%
“…Studies that directly manipulate relative power and expectancies within a single design, however, are relatively uncommon. The few studies that do so support the notion that perceivers who hold power over their targets are more likely to obtain interpersonal expectancy or behavioral confirmation effects (Copeland, 1994;Georgesen & Harris, 2000;Harris, Lightner, & Manolis, 1998).…”
Section: The Self-fulfilling Nature Of Legitimizing Mythsmentioning
confidence: 97%
“…In fact, most previous experiments either offered no explanation for role assignments (e.g., Dépret & Fiske, 1999;Georgesen & Harris, 2000;Goodwin, Gubin, Fiske, & Yzerbyt, 2000, Studies 1-3; Kipnis, 1972;Richeson & Ambady, 2003;Stevens & Fiske, 2000) or assigned roles on an explicitly random basis (e.g., Anderson & Berdahl, 2002, Study 1;Bruins, Ellemers, & De Gilder, 1999;Copeland, 1994;Guimond, Dambrun, Michinov, & Duarte, 2003, Study 4;Sachdev & Bourhis, 1985, 1991. But, to properly understand power's effects, it is important not only to consider whether a person or group has power, but also to consider what explanation, if any, was given for their situation.…”
Section: Effects Of Power Explanations On the Powerful And The Powerlessmentioning
confidence: 98%